2016
DOI: 10.14326/abe.5.94
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Activation Time on Hemodynamic Parameters: a Simulation Study

Abstract: Ventricular activation time (AT [ms]) is the time required to activate the ventricle electrically. The in uences of AT on hemodynamics are of interest in clinical studies on methods for improving left ventricle (LV) function. However, the cardiovascular system is a dynamic system, in which many parameters are interrelated with each other, and teasing out the causality of the effects of AT within the system experimentally is dif cult. In this research, we focused on analyzing the effects of changing AT on hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…To simplify the mathematical analysis, we simplified the hemodynamic model proposed by Utaki et al [49, 45] for two points. First, LV wall thickness was fixed at a constant length, and second, the relation between the LV internal radius ( R l,v ) and LV volume ( V l,v ) was simplified to linear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To simplify the mathematical analysis, we simplified the hemodynamic model proposed by Utaki et al [49, 45] for two points. First, LV wall thickness was fixed at a constant length, and second, the relation between the LV internal radius ( R l,v ) and LV volume ( V l,v ) was simplified to linear.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, a simplified hemodynamic model proposed by our group [49, 45] was used for mathematical analysis. The model was constructed from a circulation model, a LV geometry model, and a muscle contraction model.…”
Section: Model and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, a simplified hemodynamic model proposed by our group [ 24 , 25 ] was used for mathematical analysis. The model was constructed from a circulation model, a LV geometry model, and a muscle contraction model.…”
Section: Model and Definitionsmentioning
confidence: 99%
“…Utaki et al [ 24 , 25 ] used the following reported data to define the relation between R lv and L . Rodriguez et al [ 31 ] measured the time course of canine LV sarcomere length, and Sabbah et al measured the time course of the canine LV internal diameter [ 32 ].…”
Section: Model and Definitionsmentioning
confidence: 99%